2011
DOI: 10.1007/s10194-011-0295-7
|View full text |Cite
|
Sign up to set email alerts
|

Does visual cortex lactate increase following photic stimulation in migraine without aura patients? A functional 1H-MRS study

Abstract: Proton magnetic resonance spectroscopy (1H-MRS) has been used in a number of studies to assess noninvasively the temporal changes of lactate (Lac) in the activated human brain. Migraine neurobiology involves lack of cortical habituation to repetitive stimuli and a mitochondrial component has been put forward. Our group has recently demonstrated a reduction in the high-energy phosphates adenosine triphosphate (ATP) and phosphocreatine (PCr) in the occipital lobe of migraine without aura (MwoA) patients, at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 36 publications
1
53
0
Order By: Relevance
“…Additionally, low magnesium levels were observed during migraine attacks without changes in pH i (7). These early 31 P-MRS studies in migraine failed to support the prevailing concept at that time that migraine pain was caused by brain ischemic acidosis, but rather suggested a disordered energy metabolism during a migraine attack.…”
Section: Ictal Changesmentioning
confidence: 90%
See 1 more Smart Citation
“…Additionally, low magnesium levels were observed during migraine attacks without changes in pH i (7). These early 31 P-MRS studies in migraine failed to support the prevailing concept at that time that migraine pain was caused by brain ischemic acidosis, but rather suggested a disordered energy metabolism during a migraine attack.…”
Section: Ictal Changesmentioning
confidence: 90%
“…Montagna et al performed 31 P-MRS in a large cohort of migraine patients including MwoA patients, MwA patients and a group of 'complicated' migraine patients, the latter comprising both migrainous stroke and migraine with prolonged aura (9).…”
Section: Migraine Subtypes and Attack Frequencymentioning
confidence: 99%
“…In a retrospective study on patients with subacute daily headache (1-4 weeks durations), we observed that patients with a prior history of febrile illness are more likely to have neck pain and signs of meningismus (in addition to headache). 4 Our observation, 4 Almazov and Brand's observation, 2 and a few other observations 5 suggest a possibility of postinfectious pathology (most likely immunological) in meninges in patients who have a prior history of infections before the onset of headache. We further suggest that the interrelation between meninges and infections may be like the interrelation of synovial membrane to various viral infections for the development of reactive arthritis, as synovial membranes and meninges are of same type of tissue (membranous connective tissue).…”
Section: New Daily Persistent Headache: Disease or Syndrome?mentioning
confidence: 50%
“…We further suggest that the interrelation between meninges and infections may be like the interrelation of synovial membrane to various viral infections for the development of reactive arthritis, as synovial membranes and meninges are of same type of tissue (membranous connective tissue). 4 We speculate a local immune reaction in the meninges in a subset of patients with NDPH who have a prior history of febrile illness. Moreover, as immune reaction may begin within 2 days after an antigenic challenge, postinfectious symptoms may start within febrile periods.…”
Section: New Daily Persistent Headache: Disease or Syndrome?mentioning
confidence: 85%
See 1 more Smart Citation